Experimental and Numerical Evaluation of Rock Dynamic Test with Split-Hopkinson Pressure Bar - Kang Peng; Ke Gao; Jian Liu; Yujiao Liu; Zhenyu Zhang; Xiang Fan; Xuyan Yin; Yongliang Zhang; Gun Huang (Advances in Materials Science and Engineering)
Feasibility of rock dynamic properties by split-Hopkinson pressure bar (SHPB) was experimentally and numerically evaluated with ANSYS/LS-DYNA. The effects of different diameters, different loading rates, and different propagation distances on wave dispersion of input bars in SHPB with rectangle and half-sine wave loadings were analyzed. The results show that the dispersion effect on the diameter of input bar, loading rate, and propagation distance under half-sine waveform loading is ignorable compared with the rectangle wave loading. Moreover, the degrees of stress uniformity under rectangle and half-sine input wave loadings are compared in SHPB tests, and the time required for stress uniformity is calculated under different above-mentioned loadings. It is confirmed that the stress uniformity can be realized more easily using the half-sine pulse loading compared to the rectangle pulse loading, and this has significant advantages in the dynamic test of rock-like materials. Finally, the Holmquist-Johnson-Concrete constitutive model is introduced to simulate the failure mechanism and failure and fragmentation characteristics of rock under different strain rates. And the numerical results agree with that obtained from the experiment, which confirms the effectiveness of the model and the method.